Effects of natural and Marangoni convections on melting of high-temperature encapsulated phase change material under the earth and the moon gravities. (25th January 2022) - Sun, Y.S.; Xu, J.Y.; Wang, H.J.; Hong, F.J.; Kita, Hideki
Highlights: The melting of high-temperature (NaNO3 @ Al2 O3 ) is numerically studied. Melting front and surface of PCM are tracked by enthalpy-porosity and CLSVOF method. Melting characteristics under Marangoni and Natural convections are analyzed. Marangoni convection (MC) mainly affects early and middle stages of melting. Relative importance of MC increases as EPCM diameter and gravity decreases. Abstract: The understanding of melting characteristics and mechanism of high temperature encapsulated phase change material (EPCM) is important for its application in heat storage systems. In this study, a two-dimensional axisymmetric numerical model is established to simulate the melting of spherical EPCMs with air void on the top. Besides buoyancy driven natural convection, Marangoni convection due to the thermocapillary force at the air-molten PCM interface is considered for the first time in this topic. To estimate thermocapillary force more accurately, the air-PCM interface is tracked by the coupled level-set and VOF method. The numerical simulations are conducted for EPCMs with Al2 O3 shell and NaNO3 core with the different EPCM diameters and under the different gravity levels. It is found that Marangoni convection mainly affects the early and middle stages of PCM melting process, and its importance relative to buoyancy driven natural convection increases as the diameter of EPCM and gravity level decreases. For the EPCMs with diameter greater than 24 mm under the earth gravity, Marangoni convection has negligible effect, while for 12 mm diameter EPCM under the moon gravity, the complete melting time could be 19% shorter under the additional role of Marangoni convection. The solid PCM profile, fluid flow structure, melting ratio and heat transfer rate during the melting of EPCM under the effects of natural convection and Marangoni convection are also analyzed in detail.